Port connectivity in a logistic network: The case of Bohai Bay, China. (November 2016) - Wang, Grace W.Y.; Zeng, Qingcheng; Li, Kevin; Yang, Jinglei
Highlights: An integrated port connectivity index is established. Emphasize hinterland access, feeder connection, and international connectivity. Assess advantages/challenges of ports in a dynamic interconnected environment. Abstract: While traditional port literature uses origin and destination pairs in global shipping networks, recent developments of dry ports in the hinterland, feeder service networks, and heavy foreign trade traffic make the ports in Bohai Bay a unique case in the analysis of inter-port connectivity and competitiveness. Using an integrated port connectivity index to define the above features, the advantages and challenges of individual ports can be assessed in a dynamic interconnected environment. The model can provide unbiased port development strategies for each port to ensure long-term sustainability.